STRATEGI INDONESIA DALAM IMPLEMENTASI KONSEP BLUE ECONOMY TERHADAP PEMBERDAYAAN MASYARAKAT PESISIR DI ERA MASYARAKAT EKONOMI ASEAN - Rendi Prayuda (Indonesian Journal of International Relations, 2019)
Abstract The development of technology and industrialization in the economy today are two things that contradict the preservation of the world's environment. The concept of sustainable development is one of the efforts to preserve the environment. Indonesia is one of the countries that supports the implementation of the concept of sustainable development, one of the steps being the concept of blue economy. As a maritime country, Indonesia has considerable biodiversity, so the Blue Economy concept is seen as more efficient. because it tries to offer solutions to the challenges of the world economy with a system that tends to be exploitative for patterns of management in the marine and fisheries sector that can currently be recognized as still not optimal. This article uses the concept of blue economy theory with descriptive qualitative research methods. The implementation of the concept of blue economy in community empowerment in coastal areas is carried out by revitalizing sustainable development by using the concept of aquaculture digitalization to support food independence and maritime security through the development of downstream fisheries products that are competitive and innovative to support Indonesia's sustainable national development.